Application of Statistical Experimental Design and Surface Plot Technique to Optimize Oxygenated Apatite Synthesis. (24th June 2020) - Belouafa, Soumia; Chaair, Hassan; Digua, Khalid
Abstract : This work deals with oxygenated apatite synthesis from calcium chloride and phosphoric acid using a wet precipitation method. An experimental design is applied to precise the influence of the synthesis parameters (pH of the reaction medium, atomic ratio Ca/P of the reagents, concentration of the calcium solution (Ca 2+ ), temperature of the reaction medium (T), and duration of the reaction (D)) on the chemical composition (Ca/P molar ratio, % O2, and % O 2 2 − ). An empirical model was developed and validated by applying the ANOVA analysis incorporating the interaction effects of all parameters and optimized using the response surface methodology. A reproducible synthesis of more oxygenated apatite with speed of dissolution adaptable to that of the osseous neoformation and allowing a progressive diffusion of oxygenated species (Ca/P = 1.575) is attained.